The unmaking of Malaysia insider's reminiscences of UMNO, Razak, and Mahathir - Ahmad Mustapha Hassan (Strategic Information and Research Development Centre, 2007)
This book is unique in that it is the product of the writer's personal experiences over nearly half a decade. It should appeal to anyone interested in Malaysian politics, particularly those who want fresh and critical insights into the administrations of Tun Razak and Dr Mahathir.